Development of gender inequality in self-rated health in the life-phase of raising children in Germany from 1994 to 2018 - A decomposition analysis of socioeconomic, psychosocial and family-related influencing factors - Frauke-Marie Tübbecke; Jelena Epping; Batoul Safieddine; Stefanie Sperlich (Elsevier, 2022)
Extensive research has documented gender inequalities in self-rated health (SRH) to the disadvantage of women. However, little research has been done on how this gender gap has changed against the backdrop of social change. Using data from the German Socio-Economic Panel Study (GSOEP), this study addressed this issue and examined time-trends in SRH between 1994 and 2018 in women (n = 117,608) and men (n = 101.404) aged 30-49 years. In addition, we analyzed the role of socioeconomic, psychosocial and family-related factors as possible mediators influencing these trends. We performed logistic regression analyses for analyzing the time-trends and applied the Karlson-Holm-Breen (KHB) method for decomposing the time effect into direct and indirect parts via mediators.Over time, the chance of reporting good as well as poor SRH remained largely stable in both genders while the majority of socioeconomic and psychosocial factors pointed towards improvement. The decomposition analysis revealed a positive effect of most of these mediators on the time trend in SRH. After controlling for the mediators, the health trend became negative, leading to a decline in the proportion of good health over time by 5.4%-point and 4.3%-point in women and men, respectively. The same pattern was observed with respect to poor SRH. For both genders, the decline of economic worries and the rise in school education contributed most to the indirect time effect.Our findings indicate a positive development of key socioeconomic and psychosocial health determinants particularly for women, but no corresponding increase in SRH. Thus, gender inequality in SRH remained largely unchanged. However, our results suggest that SRH would have developed much worse if there had been no improvements in the health determinants considered. Further studies are needed to determine what other factors may have counteracted a positive health trend and stood in the way of narrowing the gender health gap.